Hanoi's war an international history of the war for peace in Vietnam - Nguyen, Lien-Hang T., 1974- (New Cold War history., 2012)
"While most historians of the Vietnam War focus on the origins of U.S. involvement and the Americanization of the conflict, Lien-Hang T. Nguyen examines the international context in which North Vietnamese leaders pursued the war and American intervention ended. This riveting narrative takes the reader from the marshy swamps of the Mekong Delta to the bomb-saturated Red River Delta, from the corridors of power in Hanoi and Saigon to the Nixon White House, and from the peace negotiations in Paris to high-level meetings in Beijing and Moscow, all to reveal that peace never had a chance in Vietnam."--Publisher's description.